2001
DOI: 10.1111/j.1474-919x.2001.tb04180.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood parasites of birds: a plea for more cautious terminology

Abstract: There is currently much interest in parasites of birds and the possible significance of certain of these parasites in host survival and productivity (Cooper 1989). Many studies have concentrated on blood parasites, such as Huemoproteus and Leucocytozoon, and a number of relevant papers have appeared in Ibis and elsewhere.We have noted an increasing tendency for authors who have examined blood smears of birds and failed to find parasites to state that haematozoa were 'absent' in the samples or, sometimes, even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Microscopic examination of blood smears by Steadman et al (1990) (used for PCR in this study) revealed no parasites in introduced or indigenous birds on the Cook Islands. This could be due to low-intensity peripheral parasitemia and is consistent with some previous studies comparing PCR and blood smears (Cooper & Anwar 2001;Jarvi et al 2002;Richard et al 2002). The Jarvi et al (2002) study is particularly relevant, as these authors found a haematozoan prevalence of 59% of 188 birds of eight species in Samoa versus and 0% from 214 smears evaluated.…”
Section: Discussion (A) Prevalence Of Parasitessupporting
confidence: 89%
“…Microscopic examination of blood smears by Steadman et al (1990) (used for PCR in this study) revealed no parasites in introduced or indigenous birds on the Cook Islands. This could be due to low-intensity peripheral parasitemia and is consistent with some previous studies comparing PCR and blood smears (Cooper & Anwar 2001;Jarvi et al 2002;Richard et al 2002). The Jarvi et al (2002) study is particularly relevant, as these authors found a haematozoan prevalence of 59% of 188 birds of eight species in Samoa versus and 0% from 214 smears evaluated.…”
Section: Discussion (A) Prevalence Of Parasitessupporting
confidence: 89%
“…A 200· lens was used to look for extracellular parasites in one half of each smear. Intracellular stages of haematoza were sought at 400· but, in contrast to the usual method (see, for instance, Merino and Potti 1995), we scanned the whole smear following the recommendations of Cooper and Anwar (2001). The oil immersion objective was used when a possible parasite was located at 400·.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, we used the presence or absence of any blood parasite found in blood smears as an indicator of an acute infection with blood parasites. Since we were not interested in birds with very low parasitaemia, we worked under the assumption that blood smears screened for a fixed time (30 min in the present study) are an appropriate tool by which to detect acute infections, although we must accept the fact that infections detectable at only certain times of day may have been missed (see Cooper and Anwar 2001).…”
Section: Passerinesmentioning
confidence: 99%